2017
DOI: 10.1080/13880209.2017.1299769
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Cassia tora leaves in experimental cataract by modulating intracellular communication, membrane co-transporters, energy metabolism and the ubiquitin-proteasome pathway

Abstract: Context: Cataract is the clouding of eye lens which causes impairment in vision and accounts for the leading factor of global blindness. Functional food-based prevention of cataract finds application in vision research because of its availability and easy access to all classes of the society. Cassia tora Linn. (Caesalpinaceae) is an edible plant mentioned in the traditional systems of medicine for whole body health, especially to the eyes.Objective: The present study evaluates the potential of ethyl acetate fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Seed extract induced subacute toxicity including hepatotoxicity in mice [109] . Raw pod and seed caused poisoning in children in India affecting the hepatic, skeletal, brain system and resulting in fatal coma [14] Hepatitis, meningitis, COVID-19, yellow fever, poliomyelitis Cassia tora Leaves and seeds are used as a liver tonic, antimicrobial, skin diseases, fever, and cardiotonic in Ayurveda [ 110 , 111 ] Dried seed extract inhibited replication SARS-CoV replication [112] The ethanol seed extracts did not induce subchronic toxicity effect on biochemical parameters of rat [113] Hepatitis, meningitis, yellow fever Chasmanthera dependens Hochst. Used to treat infectious diseases, pain, malaria, epilepsy, convulsions and fractures in Nigeria and West Africa [114] Aqueous and methanol extract of leaf, root and stem did not exhibit any chronic toxicity on rats [115] Poliomyelitis, meningitis Chenopodium ambrosioides L. Used to treat fever in Morocco and as treatment for lung and fungal infection in West Africa [ 116 , 117 ] Induced antiviral activity against HSV-1 [118] High doses of 12.31–31.89 g/kg caused lung congestion and necrosis of the kidney tubules [117] Poliomyelitis, Meningitis Cordia africana Lam.…”
Section: Discussionmentioning
confidence: 99%
“…Seed extract induced subacute toxicity including hepatotoxicity in mice [109] . Raw pod and seed caused poisoning in children in India affecting the hepatic, skeletal, brain system and resulting in fatal coma [14] Hepatitis, meningitis, COVID-19, yellow fever, poliomyelitis Cassia tora Leaves and seeds are used as a liver tonic, antimicrobial, skin diseases, fever, and cardiotonic in Ayurveda [ 110 , 111 ] Dried seed extract inhibited replication SARS-CoV replication [112] The ethanol seed extracts did not induce subchronic toxicity effect on biochemical parameters of rat [113] Hepatitis, meningitis, yellow fever Chasmanthera dependens Hochst. Used to treat infectious diseases, pain, malaria, epilepsy, convulsions and fractures in Nigeria and West Africa [114] Aqueous and methanol extract of leaf, root and stem did not exhibit any chronic toxicity on rats [115] Poliomyelitis, meningitis Chenopodium ambrosioides L. Used to treat fever in Morocco and as treatment for lung and fungal infection in West Africa [ 116 , 117 ] Induced antiviral activity against HSV-1 [118] High doses of 12.31–31.89 g/kg caused lung congestion and necrosis of the kidney tubules [117] Poliomyelitis, Meningitis Cordia africana Lam.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous evidence has revealed a number of drugs that affected the activity of CYP450s and induced adverse interactions [13][14][15][16]. Obtusofolin is the main extraction of Catsia tora L., which has been widely applied in the ophthalmology prescription in the clinic [17]. Obtusofolin has also been demonstrated to possess various pharmacological effects making its clinical use more widely.…”
Section: Discussionmentioning
confidence: 99%
“…Cassiae semen (CS), the seed of Cassia obtusifolia L. or Cassia tora L. of the family Leguminosae, was initially recorded in the earliest book of Chinese materia medica "Shennong Bencao Jing" and described for treating dizziness and headache, improving vision, and nourishing the liver [4]. Modern pharmacological studies reported the therapeutic potential of Cassia tora leaves in preventing cataracts [5,6]. It has been revealed that anthraquinone compounds, including obtusin, emodin, and aloe emodin, are the main bioactive components in CS [7][8][9].…”
Section: Introductionmentioning
confidence: 99%